Senescence promotes in vivo reprogramming through p16INK4a and IL‐6. Issue 2 (27th December 2017) - Mosteiro, Lluc; Pantoja, Cristina; de Martino, Alba; Serrano, Manuel
Summary: Cellular senescence is a damage response aimed to orchestrate tissue repair. We have recently reported that cellular senescence, through the paracrine release of interleukin‐6 (IL6) and other soluble factors, strongly favors cellular reprogramming by Oct4, Sox2, Klf4, and c‐Myc (OSKM) in nonsenescent cells. Indeed, activation of OSKM in mouse tissues triggers senescence in some cells and reprogramming in other cells, both processes occurring concomitantly and in close proximity. In this system, Ink4a/Arf ‐null tissues cannot undergo senescence, fail to produce IL6, and cannot reprogram efficiently; whereas p53 ‐null tissues undergo extensive damage and senescence, produce high levels of IL6, and reprogram efficiently. Here, we have further explored the genetic determinants of in vivo reprogramming. We report that Ink4a, but not Arf, is necessary for OSKM‐induced senescence and, thereby, for the paracrine stimulation of reprogramming. However, in the absence of p53, IL6 production and reprogramming become independent of Ink4a, as revealed by the analysis of Ink4a/Arf/p53 deficient mice. In the case of the cell cycle inhibitor p21, its protein levels are highly elevated upon OSKM activation in a p53‐independent manner, and we show that p21 ‐null tissues present increased levels of senescence, IL6, and reprogramming. We also report that Il6 ‐mutant tissues are impaired in undergoing reprogramming, thus reinforcing the critical role of IL6 in reprogramming. Finally, young female mice present lower efficiency of in vivo reprogramming compared to male mice, and this gender difference disappears with aging, both observations being consistent with the known anti‐inflammatory effect of estrogens. The current findings regarding the interplay between senescence and reprogramming may conceivably apply to other contexts of tissue damage.